3 - Vulnerability and resilience of female farmers in Oku, Cameroon, to Climate Change - Matilda Azong,; Clare J. Kelso,; Kammila Naidoo, (African Sociological Review, 2018)
The experience of climate change is filtered through ones existing cultural, social and economic vulnerabilities. The rural poor in natural resource dependent communities in various African countries are likely to be negatively affected by climate change. In many cultures female farmers are considerably worse off than their male counterparts. This study makes use of a life history methodology in order to examine the particular nature of the vulnerability experienced by rural women in Oku in the Bamenda Highlands region of Cameroon. Gender is linked to vulnerability through a number of factors. These include access to and control over land, division of labour, marriage relationships, access to education and responsibility for dependents. Participants’ life histories show how vulnerability in the region develops over time and is both complex and non-linear. Nevertheless, the participants expressed how they used their agency, both individual and collective, in coping with vulnerability. They narrate different adaptation strategies employed including livelihood diversification, and changing farming practices. Understanding the role of gender in shaping women’s vulnerability is useful in informing the design and implementation of adaptation policies. This article makes an empirical contribution to the discussions on the need to engender climate change research, policy and actions.